PILIHAN RASIONAL PETANI GAMBIR DALAM MEMILIH PT. SUMATERA RESOURCES INTERNATIONAL SEBAGAI MITRA (STUDI DI DESA MANGGILANG KECAMATAN PANGKALAN KOTO BARU KABUPATEN LIMA PULUH KOTA) - Fitri Rahmadhani; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research conducted inManggilangVillage, PangkalanKotoBaruDistrict, Lima Puluh KotaRegency.The purpose of this research is to find out: 1) the production process of processing gambier leaves into gambier and picking gambir leaves which are sold directly, 2) the rational choice of gambir farmers. This research uses descriptive quantitative method.The data collection techniques in this study were observation, questionnaires, and documentation.This study uses a census technique, where there are 60 respondents. The data analysis technique in this research is descriptive quantitative using SPSS version 26. Based on the results of the study, it can be concluded that the processing of leaves into gambier takes time to process. Meanwhile, the process of picking gambir leaves can be directly sold on that day. Most of the income earned is obtained from picking rather than processing gambier leaves into gambier. There are 51 respondents who experienced an increase in income by selling gambier leaves, the remaining 9 respondents did not experience a significant change in their income. Furthermore, 46 respondents also reduced the number of farm workers working on their land, but there were 14 other respondents who did not experience a change between processing gambier leaves into gambier and selling gambier leaves. Keyword: Rational Choice, Gambir Processing, Farmers